Transformasi Digital UMKM Batik Melalui Penerapan Teknologi IT Berbasis Sistem Katalog - Musalim Yusuf; Raisah Fajri Aula; Tio Risnanto; Faradj Farizi (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
Digital transformation is one of the important steps for MSMEs (Micro, Small, and Medium Enterprises) in facing the era of globalization and market competition, especially in the creative economy sector such as batik. This study aims to analyze the digital transformation strategy of MSME Batik Banyumasan through the application of IT technology based on a catalog system. The research method used is qualitative with an observation, interview, and SWOT analysis approach to understand the needs and challenges faced by business actors. The results of the study show that the application of a catalog website can increase customer attraction and facilitate the marketing process of batik products. This website is equipped with features such as a homepage, new products, collections, and complete products designed to make it easier for visitors to explore and buy batik products. This study concludes that digital transformation through technology based on a catalog system not only helps MSME Batik Banyumasan in increasing sales, but also preserves the cultural heritage of batik as part of the creative economy.